Cost-effectiveness of iron supplementation and malaria chemoprophylaxis in the prevention of anaemia and malaria among Tanzanian infants - M. Alonso González; C Menéndez; F Font; E Kahigwa; J Kimario; H Mshinda; M Tanner; X Bosch-Capblanch; P.L Alonso (The World Health Organization, 2000)
Prerequisites for effective interventions against severe anaemia and malaria among infants are economic evaluations to aid the setting of priorities and the making of health policy. In the present study we analysed the cost and effectiveness of three control strategies hypothetically delivered through the Expanded Programme on Immunization (EPI). For the prevention of severe anaemia and from the perspective of the health provider, the cost-effectiveness ratios were, respectively, US$ 8, US$ 9, and US$ 21 per disability-adjusted life year (DALY) for malaria chemoprophylaxis with Deltaprim (a combination of 3.125 mg pyrimethamine and 25 mg dapsone) + iron, Deltaprim alone, or iron supplementation alone. For malaria prevention, Deltaprim + iron cost US$ 9.7 per DALY and Deltaprim alone cost US$ 10.2 per DALY. From a sociocultural perspective the cost-effectiveness ratios ranged from US$ 9 to US$ 26 for severe anaemia prevention and from US$ 11 to US$ 12 for the prevention of clinical malaria. These ratios were highly cost-effective, as defined by the World Bank's proposed threshold of less than US$ 25 per DALY for comparative assessments. Furthermore, all the preventive interventions were less costly than the current malaria and anaemia control strategies that rely on clinical case management. This economic analysis supports the inclusion of both malaria chemoprophylaxis and iron supplementation delivered through EPI as part of the control strategies for these major killers of infants in parts of sub-Saharan Africa.